The Current Rise of Artificial Intelligence and Religious Studies: Some Reflections Based on ChatGPT - Yuli Andriansyah (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2023)
In recent months, there has been a remarkable surge in artificial intelligence (AI) development, with ChatGPT emerging as a notable application. ChatGPT, an OpenAI chatbot, achieved an impressive milestone of 100 million monthly active users within two months of its launch in January, making it the fastest-growing consumer application to date. Experts predict that AI will significantly impact 50 percent of businesses in the next five years. ChatGPT has already showcased its versatility in the medical field, aiding in tasks like medical exam preparation and serving as an in-office scribe. As its potential in healthcare continues to expand, ChatGPT holds promising prospects for the future. Additionally, research on AI and religion is gaining traction, exploring topics such as ethical implications, integration into religious practices, analysis of religious texts, interfaith dialogue facilitation, and the theological impact of AI on creation. The increasing number of scholarly publications on the subject indicates a growing interest in exploring the complex relationship between artificial intelligence and religion.